The role of c-FLIP in modulation of CD95-induced apoptosis - Watzl, Carsten; Krammer, Peter H.; Peter, Marcus E. (The journal of biological chemistry, 1999)
Upon stimulation, CD95 (APO-1/Fas) recruits the adapter molecule Fas-associated death domain protein (FADD)/MORT1 and caspase-8 (FADD-like interleukin-1β-converting enzyme (FLICE)/MACH/MCH5) into the death-inducing signaling complex (DISC). Recently, a molecule with sequence homology to caspase-8 was identified, termed cellular FLICE-inhibitory protein (c-FLIP). c-FLIP has been controversially reported to possess apoptosis-promoting and -inhibiting functions. Using c-FLIP-specific monoclonal antibodies, we now show that c-FLIP is expressed in two isoforms, both of which, like FADD and caspase-8, are recruited to the CD95 DISC in a stimulation-dependent fashion. In stably transfected BJAB cells, c-FLIP blocks caspase-8 activation at the DISC and thereby inhibits CD95-mediated apoptosis. During this process, both caspase-8 and c-FLIP undergo cleavage between the p18 and p10 subunits, generating two stable intermediates of 43 kDa that stay bound to the DISC. c-FLIP has been suggested to play a role in protecting activated peripheral T cells from CD95-mediated apoptosis (Irmler, M., Thome, M., Hahne, M., Schneider, P., Hofmann, K., Steiner, V., Bodmer, J. L., Schroter, M., Burns, K., Mattmann, C., Rimoldi, D., French, L. E., and Tschopp, J. (1997) Nature 388, 190-195). In contrast to this hypothesis, neither caspase-8 nor c-FLIP were cleaved in these cells, ruling out c-FLIP as the main factor regulating DISC activity. Moreover, recruitment of FADD, caspase-8, and c-FLIP to the DISC was strongly reduced in the apoptosis-resistant but readily detectable in the apoptosis-sensitive T cells.